2015
DOI: 10.1093/nar/gkv541
|View full text |Cite
|
Sign up to set email alerts
|

Gene target specificity of the Super Elongation Complex (SEC) family: how HIV-1 Tat employs selected SEC members to activate viral transcription

Abstract: The AF4/FMR2 proteins AFF1 and AFF4 act as a scaffold to assemble the Super Elongation Complex (SEC) that strongly activates transcriptional elongation of HIV-1 and cellular genes. Although they can dimerize, it is unclear whether the dimers exist and function within a SEC in vivo. Furthermore, it is unknown whether AFF1 and AFF4 function similarly in mediating SEC-dependent activation of diverse genes. Providing answers to these questions, our current study shows that AFF1 and AFF4 reside in separate SECs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 42 publications
8
75
1
Order By: Relevance
“…In contrast, the activated elongation in JQ1-treated cells was completely gone only after the KO of AFF1 but not AFF4 (Fig. 3C), reinforcing the notion that JQ1 acts primarily by stimulating the Tat/SEC-dependent HIV-1 elongation and that the AFF1-SEC is preferentially utilized in this process (11,17,18). As for HIV-1 elongation in cells treated with either PMA or prostratin, it was similarly sensitive to the loss of AFF1 or AFF4, although the dependence of the two compounds on AFF1/4 was a few orders of magnitude lower than that of JQ1 on AFF1 (Fig.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…In contrast, the activated elongation in JQ1-treated cells was completely gone only after the KO of AFF1 but not AFF4 (Fig. 3C), reinforcing the notion that JQ1 acts primarily by stimulating the Tat/SEC-dependent HIV-1 elongation and that the AFF1-SEC is preferentially utilized in this process (11,17,18). As for HIV-1 elongation in cells treated with either PMA or prostratin, it was similarly sensitive to the loss of AFF1 or AFF4, although the dependence of the two compounds on AFF1/4 was a few orders of magnitude lower than that of JQ1 on AFF1 (Fig.…”
Section: Resultssupporting
confidence: 72%
“…4C). Previously, it has been shown that JQ1 activates HIV-1 transcription and reverses viral latency through mostly the Tat/SEC-dependent pathway (17,18) and that the SEC subunits ELL2 and AFF1 play an especially important role in this process (9,11). Given these revelations, it is likely that the extra ELL2 or AFF1 introduced into the AFF4 KO cells was used to assemble the Tat-friendly, ELL2/AFF1-containing SECs that efficiently promoted latency reversal in the absence of AFF4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations